Micro-analytical GO/HRP bioreactor for glucose determination and bioprocess monitoring - Vojinović, V. (2020)
A bi-enzymatic micro-analytical bioreactor integrated in a FIA system for glucose measurements is described. Its robustness and small dimensions (working volume of about 70 μl containing approximately 1.2 mg GO and 0.26 mg HRP) make it easy to operate. The column is based on immobilisation of glucose oxidase (GO) and horseradish peroxidase (HRP) on alkylamine controlled pore glass (CPG) beads. The column has excellent shelf life (no significant loss of activity after 1 year if kept at 4 °C), and a very high operational stability that was demonstrated through extensive usage for glucose determinations over 1 year period during which the column retained almost all of its activity. More importantly, this operational stability allows glucose monitoring in the culture media without a decay of signal over the experiment time and consequently no signal correction or re-calibration is needed. This high operational stability was also confirmed by continuous glucose conversion with 30% activity loss after converting quantity of glucose equivalent to 21600 FIA injections of 20 μl with 1.7 mM glucose. Such good performance is a result of an optimised immobilisation method and moreover of the implementation of in situ enzyme stabilisation strategy which consisted on promoting the instantaneous H2O2 consumption produced by the GO. This strategy has the additional advantage of allowing concomitant assay of the H2O2 based on the HAP catalysed co-oxidation of phenol-4-sulphonic acid (PSA) in the presence of 4-aminoantipyrine (4-AAP). The glucose measurements are reproducible with high precision against the standard HPLC method. Linear range and sensitivity depend on sample injection volume; the upper limit is about 1.1 g/l. Lower detection limit is 10 mg/l. The column performance has been validated for E. coli and S. cerevisiae fermentation monitoring, and glucose measurements in an animal cell culture (rat Langerhans islets).